Konflik Politik pada Novel Hanum: Analisis Wacana Kritis - Feni M. Muksin (Kantor Bahasa Provinsi Maluku Utara, 2018)
In general, this study focused on political conflict in the Hanum novel by Mustofa W. Hasyim due to the practice of power. The focus of this research is elaborated into three, namely (1) the power practice in the legal sector, (2) the power practice in the economic sector, and (3) the power practice in the cultural sector. Its aim is to reveal political conflicts due to the practice of power in the novel. The type of research is qualitative with Norman Fairclough's critical discourse analysis approach. The political conflict in Hanum's novel arose due to the practice of power in the legal, economic and cultural sectors. Its appears as experiential, relational, and expressive values in the text and participants. The participants demonstrate beliefs, social identity, and social relations through the use of declarative and interrogative sentences and the use of metaphors.